Ultrafast Brain Magnetic Resonance Imaging in Acute Neurological Emergencies: Diagnostic Accuracy and Impact on Patient Management. Issue 3 (March 2020) - Kazmierczak, Philipp M.; Dührsen, Max; Forbrig, Robert; Patzig, Maximilian; Klein, Matthias; Pomschar, Andreas; Kunz, Wolfgang G.; Puhr-Westerheide, Daniel; Ricke, Jens; Solyanik, Olga; Cyran, Clemens C.
Abstract : Objectives: The aim of this study was to investigate diagnostic accuracy and impact on patient management of an ultrafast (4:33 minutes/5 sequences) brain magnetic resonance imaging (MRI) protocol for the detection of intracranial pathologies in acute neurological emergencies. Materials and Methods: Four hundred forty-nine consecutive emergency patients with acute nontraumatic neurological symptoms were evaluated for this institutional review board–approved prospective single-center trial. Sixty patients (30 female, 30 male; mean age, 61 years) with negative head CT were included and underwent emergency brain MRI at 3 T subsequent to CT. MRI included the ultrafast protocol (ultrafast-MRI; sag T1 GRE, ax T2 TSE, ax T2 TSE Flair, ax T2* EPI-GRE, ax DWI SS-EPI; TA, 5 minutes) and an equivalent standard-length protocol (TA, 15 minutes) as reference standard. Two blinded board-certified neuroradiologists independently analyzed the MRI with regard to image quality (1, nondiagnostic; 2, substantial artifacts; 3, satisfactory; 4, minor artifacts; 5, no artifacts) and intracranial pathologies. Sensitivity and specificity for the detection of intracranial pathologies were calculated accordingly. Results: Ninety-three additional intracranial lesions (acute ischemia, n = 21; intracranial hemorrhage/microbleeds, n = 27; edema, n = 2; white matter lesion, n = 38; chronic infarction, n = 3; others, n = 2) were detected by ultrafast-MRI, whereas 101 additional intracranial lesions were detected by the standard-length protocol (acute ischemia, n = 24; intracranial hemorrhage/microbleeds, n = 32; edema, n = 2; white matter lesion, n = 38; chronic infarction, n = 3; others, n = 2). Image quality was equivalent to the standard-length protocol. Ultrafast-MRI demonstrated high diagnostic accuracy (sensitivity, 0.939 [0.881–0.972]; specificity, 1.000 [0.895–1.000]) for the detection of intracranial pathologies. MRI led to a change in patient management in 10% compared with the initial CT. Conclusions: Ultrafast-MRI enables time-optimized diagnostic workup in acute neurological emergencies at high sensitivity and specificity compared with a standard-length protocol, with direct impact on patient management. Ultrafast MRI protocols are a powerful tool in the emergency setting and may be implemented on various scanner types based on the optimization of individual acquisition parameters.